2006
DOI: 10.3354/dao072193
|View full text |Cite
|
Sign up to set email alerts
|

Sub-clinical infection of farmed Atlantic salmon Salmo salar with salmonid alphavirus— a prospective longitudinal study

Abstract: A prospective longitudinal study of salmonid alphavirus infection in farmed Atlantic salmon Salmo salar L. was initiated in post-transfer smolts on a UK farm in July 2004 and continued for 320 d. Sampling was concentrated on a single caged population (C4) with serum and tissue samples collected and tested for viraemia, virus neutralising (VN) antibodies and viral nucleic acid by real time RT-PCR and by histopathology; 380 sera collected between Days 0 (D0) and 139 (D139) were consistently negative for both vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 28 publications
7
48
0
Order By: Relevance
“…It is also plausible that amplification and spread of SAV from infected fish farms could lead to the establishment of potential reservoirs of re-infection through the complexities of trade (McLoughlin et al 2003). The saithe Pollachius virens occurs in the vicinity of sea cages (Bruno & Stone 1990), and later studies have shown virus-neutralising antibodies, but have failed to record disease, suggesting that inter-species transmission from wild to farmed fish, or vice versa, can take place (Graham et al 2006). Finally, in terrestrial alphaviruses, transmission of infection is linked to an arthropod vector; however, in the fish to fish transmission of SAV, as demonstrated by Boucher et al (1995), no vector is needed as a routine route of infection, and none has been identified to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also plausible that amplification and spread of SAV from infected fish farms could lead to the establishment of potential reservoirs of re-infection through the complexities of trade (McLoughlin et al 2003). The saithe Pollachius virens occurs in the vicinity of sea cages (Bruno & Stone 1990), and later studies have shown virus-neutralising antibodies, but have failed to record disease, suggesting that inter-species transmission from wild to farmed fish, or vice versa, can take place (Graham et al 2006). Finally, in terrestrial alphaviruses, transmission of infection is linked to an arthropod vector; however, in the fish to fish transmission of SAV, as demonstrated by Boucher et al (1995), no vector is needed as a routine route of infection, and none has been identified to date.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown heart tissue to be one of the most appropriate tissues for detecting SAV during all stages of infection (also persistent infections) (Graham et al 2006, Christie et al 2007, Andersen et al 2007; for this reason, only heart tissue was processed for molecular testing. Approximately 5 mg of homogenised tissue was used for ex traction of total RNA (MagAttract M48 RNA Tissue Kit, Qiagen) using the M48 BioRobot (Qiagen).…”
Section: Sav Rt-qpcr and Sequencingmentioning
confidence: 99%
“…P. virens, G. morhua and S. scombrus in particular were observed next to the cage walls and were therefore often within 1 to 2 m of the caged salmon. The most abundant farm-associated species, P. virens, may act as a natural reservoir of the salmonid alphavirus (SAV; Graham et al 2006) and carries infectious pancreatic necrosis virus (IPNV), though at relatively low prevalence (1.1%; Wallace et al 2008). If pathogens or parasites are shared and transmitted among salmon and these 4 species, residence at specific farms followed by movements to adjacent farms may contribute to the propagation of outbreaks, in an analogous way to the dispersal of bird flu to domestic birds by migrating wild birds (Chen et al 2005).…”
Section: Potential For Wild Fish To Act As Disease Vectorsmentioning
confidence: 99%
“…However, this study did not include seasonality of movements. Subclinical infections can go unnoticed (Bruno 2004, Graham et al 2006, Lyngstad et al 2008, Murray et al 2010. Performing clinical tests increases the change of detecting subclinical infections and movements can be stopped when a farm tests positive.…”
Section: Seasonalitymentioning
confidence: 99%
“…Therefore, movements from source farms known to be infected with a notifiable disease are prohibited (Joint Government/Industry Working Group 2000). However, notifiable and other infections can go undetected (Murray & Peeler 2005, Graham et al 2006, Lyngstad et al 2008. Therefore, pathogens may spread through live fish movements before pathogens are detected (Jonkers et al 2010).…”
mentioning
confidence: 99%